Utilization of Sugarcane Bagasse Activated Carbon as an Adsorbent for the Reduction of COD and Total Chromium in Tannery Wastewater Treatment - Priska Valeria Putrisuri; Candra Dwiratna W; Sudiro Sudiro (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The leather tanning industry is a sector that processes raw hides into tanned leather using specific tanning agents and has the potential to degrade water quality due to the high concentration of organic substances, indicating that organic compounds in tannery wastewater are difficult to degrade and that heavy metal contamination is present in the effluent, particularly chromium (Cr). This study aims to determine the capability of sugarcane bagasse activated carbon in reducing COD and total chromium concentrations and to evaluate the effectiveness of adsorbent mass and contact time in reducing COD and total chromium in tannery wastewater using pre-sedimentation and adsorption methods. The study employed adsorbent mass variations of 10 g and 15 g and contact times of 90 and 150 minutes. The results showed that the sedimentation and adsorption processes reduced COD concentration by 579 mg/L (82.13%) and total chromium by 20.02% (81.74%); however, these reductions did not meet the established wastewater quality standards.